Genomic Profiling of Patient-Derived Colon Cancer Xenograft Models - Lee, Won-Suk (Medicine (Baltimore), 2014)
Recent evidence suggests that patient derived xenograft (PDX) models can maintain certain pathological and molecular features of the original disease. However, these characterizations are limited to immunohistochemistry or by tissue microarray analysis. We conducted a high-throughput sequencing of primary colon tumor and PDX has not been reported yet. Fresh primary colon cancer tissues that originate from surgery were implanted into the subcutaneous space of 6- to 8-week-old female BALB/c nu/nu or NOD/SCID mice and serially passaged in vivo. Ion AmpliSeq Cancer Hotspot Panel v2 (Ion Torrent) was used to detect frequent somatic mutations and similarity of molecular characteristics between the 10 patient tumors and matched PDX. Histologic and immunohistochemical analyses revealed a high degree of pathologic similarity including histologic architecture and expression of CEA, CK7, and CD20 between the patient and xenograft tumors. In 80% cases, all of the somatic mutations detected in primary tumor were concordantly detected in PDX models. However, 2 PDX models showed gained mutations such as PIK3CA or FBWX7 mutation. Ten patient-derived advanced colon cancer xenograft models were established. These models maintained the key characteristic features of the original tumors, suggesting useful tool for preclinical personalized medicine platform.